Effects of Tawhidic paradigm dynamism in qualitative research - Mhd. Sarif, Suhaimi (Zes Rokman Resources (2131022-P), 2018)
Qualitative research provides alternative dynamism in the contemporary intellectualism and philosophical inquiry to meet the high level of uncertainty and complexity of the world. Qualitative research has been widely accepted in all disciplines for academic as well as non-academic reasons. Qualitative research has its own uniqueness and dynamism in philosophy, paradigm, ontology, epistemology and methodology. Realism, constructionism and pragmatism paradigms have been applied widely for qualitative research. However, the mainstream research has inadequate philosophy inquiry driven by Tawhidic paradigm. This postulates that there are several effects on the dynamism of qualitative research based on Tawhidic paradigm. This study obtained feedback through personal interview from five (5) very experienced qualitative social researchers pertaining to the inclination on applying Tawhidic Paradigm. The respondents gave positive inclination on the application of Tawhidic Paradigm given the holistic, comprehensive and balanced ontology, epistemology and methodology. The feedback from the informants explained that dynamism driven by Tawhidic paradigm in qualitative research is in the research stages of describing, narrating, explaining and exploring events, individuals, groups, institutions, and organisations in the deductive manner within the parameters and measurement of Tawhid. Indeed, the dynamism Tawhidic paradigm enables for knowledge acquisition, modelling, using and retrieving in systematic and pragmatic way.